2005
DOI: 10.1007/s00417-005-1175-0
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of neuron-specific enolase and S100 protein in the subretinal fluid of rhegmatogenous retinal detachment

Abstract: Neuron-specific enolase (NSE) and S100 are known to be good markers of brain stress and, thus, are good markers of retinal stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…High NSE serum concentrations predicted poor neurological outcome in a majority of cardiac arrest patients [ 52 ]. NSE levels have also been used to predict neurological outcome in traumatic brain injury (TBI) [ 53 ] and retinal disease, such as retinal detachment [ 54 , 55 , 56 ]. Higher levels of NSE have been detected in Leber’s hereditary optic neuropathy (LHON), a mitochondrial disease affecting retinal ganglion cells (RGC) [ 56 ].…”
Section: Nse As Prognostic Factors In Patients During Neuroinflammmentioning
confidence: 99%
“…High NSE serum concentrations predicted poor neurological outcome in a majority of cardiac arrest patients [ 52 ]. NSE levels have also been used to predict neurological outcome in traumatic brain injury (TBI) [ 53 ] and retinal disease, such as retinal detachment [ 54 , 55 , 56 ]. Higher levels of NSE have been detected in Leber’s hereditary optic neuropathy (LHON), a mitochondrial disease affecting retinal ganglion cells (RGC) [ 56 ].…”
Section: Nse As Prognostic Factors In Patients During Neuroinflammmentioning
confidence: 99%
“…27,28 Also, NSE has been defined as an effective marker of axonal injury within the CNS in its early stages 29 and of brain stress in general. 30 Both S100 and NSE are clinical biomarkers used in patients with TBI. S100 and NSE levels in cerebrospinal fluid and serum can be used more or less satisfactorily to predicate the existence, absence and severity of CNS injury or brain death and the outcome of TBI patients.…”
Section: Introductionmentioning
confidence: 99%
“…Breakdown of the blood-retinal barrier following RRD results in the leakage of blood, which may promote an inflammatory reaction and the proliferation of retinal glial and RPE cells. 24,25 In previous studies, various factors involved in the inflammation process, such as gelatinase activity, 26,27 connective tissue growth factor, 28 pigment-epithelium-derived factor, 29 IL-6, 30 s-100, 31 and TGF-b2 25 have been reported to be present in SRF. In our study, ARPE-19 cells cocultured with SRF showed elevated expression of ICAM-1 in vitro.…”
Section: Resultsmentioning
confidence: 98%